Economic and non-economic determinants of Iranian pharmaceutical companies’ financial performance: an empirical study - Masoumi, Mohammadreza (BMC Health Serv Res, 2019)
BACKGROUND: The pharmaceutical industry in Iran is influenced by various parameters such as internal factors caused by the financial information of each economic unit and external factors including major economic and non-economic variables. METHODS: This study is aiming to examine the effect of such variables on the stock return of 34 pharmaceutical companies in the Tehran Securities Exchange market using quarterly data from 1995 to 2016. In this research, an autoregressive model was utilized to examine the way that variables affect the stock market index. In such patterns, there is no need for explicit short-term structural relationships and structural knowledge is extracted from causal relationships. Finally, to analyze the results, impulse-response functions, forecast error variance, and historical decomposition were collected. RESULTS: Results of this research show that positive shock to the variables, namely the currency rate, collection period of quests, and healthcare costs lead to a decrease in the return of pharmaceutical companies. On the other hand, a positive shock to the variables such as GDP, and money volume, leads to an increase in the stock return of pharmaceutical companies. CONCLUSION: Different factors contribute to the stock return of pharmaceutical companies. Among the variables examined in this study, market currency rate, money volume, pharmaceutical sector inflation, bank interest rate, GDP in the healthcare sector, healthcare costs, and collection period of quests have the most effect on describing changes within the stock return of pharmaceutical companies.